1965
DOI: 10.1042/bj0970214
|View full text |Cite
|
Sign up to set email alerts
|

The connexion between active cation transport and metabolism in erythrocytes

Abstract: 1. A study has been made of the dependence on the concentrations of internal Na(+) and external K(+) of lactate and phosphate production in human erythrocytes. 2. Lactate production was stimulated by Na(+) and K(+) but only when they were internal and external respectively. The stimulation was counteracted by ouabain. The production of phosphate was affected in the same way. 3. There is a quantitative correlation between these effects and those previously found for cation movements and the membrane adenosine t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
68
1

Year Published

1967
1967
1978
1978

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 264 publications
(78 citation statements)
references
References 45 publications
9
68
1
Order By: Relevance
“…Available experimental evidence (see Whittam & Ager, 1965) seems to indicate that the number of Na or K ions transported per pump cycle is fixed and independent of the cation concentration at either surface of the cell membrane. It seems therefore reasonable to assume that ion translocation will only take place in those pump units which have attained a certain degree (n) of occupation by Na ions.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Available experimental evidence (see Whittam & Ager, 1965) seems to indicate that the number of Na or K ions transported per pump cycle is fixed and independent of the cation concentration at either surface of the cell membrane. It seems therefore reasonable to assume that ion translocation will only take place in those pump units which have attained a certain degree (n) of occupation by Na ions.…”
Section: Resultsmentioning
confidence: 99%
“…The assumption that three Na ions have to combine with a pump unit to induce ion translocation seems to rest on a sound physical basis since all the available experimental evidence indicates that about three Na ions are transported per pump cycle by the Na pump of red cells (Glynn, 1962;Sen & Post, 1964;Whittam & Ager, 1965;Garrahan & Glynn, 1967d).…”
Section: Resultsmentioning
confidence: 99%
“…(an earlier result of Whittam & Ager (1965) is included). Differences in the lactate production from inosine and adenosine cannot explain the differences in active transport supported by these metabolites, since both produced lactate at about the same rate (5 2-5-8 #mole/ml./hr under the present conditions).…”
Section: The Effect Of Atp Concentration On Potas8ium Influxmentioning
confidence: 99%
“…Whereas, in our studies, the half-maximal activation value was 9.8 5 1.2 mM for sodium and 1.1 f 0.38 mM for potassium for adult stromal ATPase, WHITTAM and AGER [22] reported values of 15 and 2.0 mM, respectively, and POST et al [17] found values of 24 and 3.0 mM for sodium and potassium activation, respectively.…”
Section: Ratio Of Sodium-potassium-sensitive a Tpase To Magnesiumdefimentioning
confidence: 59%